The differences in perinatal outcomes between refugee and resident mother-infant dyads: A retrospective study in Turkey between 2013 and 2018 - ÖZEK, EREN; BARIŞ, HATİCE EZGİ; BORAN, PERRAN (TAYLOR & FRANCIS INC, 2022)
In this study, we aimed to examine and compare the perinatal outcomes between refugee and resident mother-infant dyads. Data of refugee women who had given birth in a university hospital (n = 924) and matched resident mother-infant dyads (n = 957) were included. Analysis revealed higher adolescent pregnancy rates and lower rates of antenatal care attendance among refugee mothers compared to residents. No significant differences in neonatal outcomes were found, except for a significantly higher number of preterm births among refugee infants. Interventions should be made to ensure antenatal care for all pregnant women, which can also prevent preterm birth.
Keywords: PREGNANCY OUTCOMES; SYRIAN REFUGEES; PRETERM BIRTH; WOMEN; RISK; CARE